2011
DOI: 10.1016/j.memsci.2010.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Pressure resistance of thin ionic liquid membranes using tailored ceramic supports

Abstract: and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their personal website or institutional repository. Authors requiring further information regarding Elsevier's archiving and manuscript policies are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…One technology that has attracted interest is the use of supported ionic liquid membranes (SILMs) for gas sweetening [19,20]. SILMs are produced by impregnating a porous membrane with a small amount of IL.…”
Section: Introductionmentioning
confidence: 99%
“…One technology that has attracted interest is the use of supported ionic liquid membranes (SILMs) for gas sweetening [19,20]. SILMs are produced by impregnating a porous membrane with a small amount of IL.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the polymeric and inorganic membranes can be used as a support. SILMs based on a ceramic support can resist elevated pressures and temperatures up to 5.5 MPa and 453 K. 50,55 Choosing a proper support with relevant pore diameters may help to decrease the chance of ILs loss from the large pores of the membrane and improve the SILMs stability. 56 Some literature data conclude that membranes with pore diameters in the range of 100-200 nm are recommended for SILMs.…”
Section: Silm Long Term Stabilitymentioning
confidence: 99%
“…Kreiter et al [81] reported that the rates of diffusion, uptake, and release might have affected the performance of SILMs because the dissolution/desorption processes play a decisive role in SILMs compared to pure ILs. Barghi [83] stated that a poly(vinylidene difluoride) (PVDF) support showed lower permeabilities of 2.7 and 0.4 Barrer for CO 2 and N 2 , respectively.…”
Section: Silmsmentioning
confidence: 99%
“…Kreiter et al reported that the rates of diffusion, uptake, and release might have affected the performance of SILMs because the dissolution/desorption processes play a decisive role in SILMs compared to pure ILs. Barghi et al fabricated SILMs by immobilizing [bmim][PF6] IL on an inorganic membrane.…”
Section: Applications Of Ils In Gas Separation Membranesmentioning
confidence: 99%